Magnetic Hyperthermia for Cancer Treatment: Main Parameters Affecting the Outcome of In Vitro and In Vivo Studies - Vânia Vilas-Boas; Félix Carvalho; Begoña Espiña (Molecules, 2020)
Magnetic hyperthermia (MHT) is being investigated as a cancer treatment since the 1950s. Recent advancements in the field of nanotechnology have resulted in a notable increase in the number of MHT studies. Most of these studies explore MHT as a stand-alone treatment or as an adjuvant therapy in a preclinical context. However, despite all the scientific effort, only a minority of the MHT-devoted nanomaterials and approaches made it to clinical context. The outcome of an MHT experiment is largely influenced by a number of variables that should be considered when setting up new MHT studies. This review highlights and discusses the main parameters affecting the outcome of preclinical MHT, aiming to provide adequate assistance in the design of new, more efficient MHT studies.